Bulbophyllum cherrapunjeensis (Orchidaceae), a new species from Meghalaya, India - Verma, Durgesh; Barbhuiya, Hussain Ahmed; Lavania, Seshu (Phytotaxa, 2014)
Bulbophyllum Petit-Thouars (1822: tab. 3) is the largest orchid genus, comprising about 1900 species, largely distributed in tropical areas of both New and Old Worlds (Chen & Vermeulen 2009). There are about 100 species in India and about 63 in northeastern India (Augustine et al 2001, Misra 2007). Kataki (1986) reported 28 species of Bulbophyllum from the state of Meghalaya. During our botanical exploration to Cherrapunjee, Meghalaya, in July 2013, we found a new species described below.